Preparation and photo-catalytic performance of β2-SiW11/PANI/TiO2 photo-catalyst. Issue 24 (11th November 2020) - Yang, Mingrui; Ma, Ronghua; Chen, Lin; Zhang, Chengli; Cao, Rui; Wen, Qi
Abstract: Using heteropoly tungstate β2 -K8 SiW11 O39 xH2 O as the active component, the tungstate was loaded on PANI/TiO2 by the dipping method to prepare a composite photo-catalyst β2 -SiW11 /PANI/TiO2 . The new ternary composite material, β2 -SiW11 /PANI/TiO2, was characterized by IR, UV, TG, XPS, XRD and SEM. Meanwhile, the degradation of methylene blue solution was used as a probe reaction to evaluate the photo-catalytic performance of β2 -SiW11 /PANI/TiO2 . The effect of solution pH and amount of composite material on photo-catalytic activity was investigated. Compared with TiO2 and silicate, the composite material β2 -SiW11 /PANI/TiO2 as photo-catalyst exhibited enhanced photo-catalytic performance due to the synergic effect between TiO2 and heteropoly tungstate. Under optimum conditions, 92.58% of the dye was decomposed in 150 min. Our present findings will have a profound effect on the use of β2 -SiW11 /PANI/TiO2 composite as photo-catalytic material. Graphical Abstract: